2012
DOI: 10.1074/jbc.m111.284091
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Tumor Differentiation Factor (TDF) Receptor from Steroid-responsive and Steroid-resistant Breast Cancer Cells

Abstract: Background: Tumor differentiation factor (TDF) is a newly identified pituitary protein with no known receptor. Results: Heat shock 70-kDa proteins are potential TDF receptor candidates. Conclusion: TDF acts on breast cells through a novel pathway. Significance: These data may help to elucidate the role of TDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 77 publications
4
60
0
Order By: Relevance
“…The biological activity of TDF on breast and prostate cancer cells has not been reproduced by any other growth factors or pituitary hormones. Its secretion from the pituitary into the bloodstream and its differentiation activity on breast and prostate cancer cells suggest that TDF may have an endocrine role [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological activity of TDF on breast and prostate cancer cells has not been reproduced by any other growth factors or pituitary hormones. Its secretion from the pituitary into the bloodstream and its differentiation activity on breast and prostate cancer cells suggest that TDF may have an endocrine role [3].…”
Section: Introductionmentioning
confidence: 99%
“…To shed some light into TDF's function, our laboratory isolated and characterized potential TDF receptor (TDF-R) candidates from breast cancer cell lines, nonbreast cancer cell lines, and from fibroblasts [3], [4]. We concluded that TDF-R candidates are members of the 70 kDa heat shock protein family (HSP70).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS-based proteomics methods [13,20,21,[27][28][29][30]. The first step in a proteomics experiment is sample fractionation, which can be done by non-denaturing biochemical approaches such as chromatography or centrifugation, or by denaturing methods such as acetone precipitation or electrophoresis (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…MS is a method that can reliably and comprehensively identify proteins and putative biomarkers [4,5,[12][13][14][15][16][17][18][19][20][21][22]. MS is already in use for newborn screening for several other disorders, including phenylketonuria, congenital hypothyroidism and cystic fibrosis [23].…”
Section: Introductionmentioning
confidence: 99%